Effect of silicon on salinity tolerance of two tomato (Lycopersicon esculentum Mill.) cultivars 1- vegetative growth characteristies - Fadhil Abbas, Muayed; Neamah Jerry, Awatif; Jubair Radhi, Nasser (Journal of Kerbala for Agricultural Sciences, 2017)
The study was conducted elwing two growing seasons (2015 and 2016) in aprivate farm in Kufa-Najaf,with the objective of improving salinity tolerance of tomato (Lycopersicon esculentum Mill.) with exogenous application of silicon. The study included 40 treatments, whil were four levels of irrigation water salinity (2.5, 5.0, 7.5 or 10 ds.m-1) , two tomato cultivars (Aulla and Majid) and five concentration of silicon (0 , 50 , 100 , 150 , or 200 mg l-1). Asplit-split plot design was used in afactorial experiment with three factors and three replicates. The results were analyzed using analysis of ariauce and treatment means were comparod using the least significant differences (LSD) at 0.05. The effect of the above treatment were studied on vegetative growth characteristies were plant length ,number of side shrots,leaf number,leaf area as well as dry weights of the shrot sytem, Irragation water salinity at 7.5 and 10.0 ds m-1 caused a significant decrease in vegetative growth characteristies for both growing seasons. Exogenous treatment with silicon caused a significant increace in all vegetative growth characteristies, for both growing seasons. As for the effect of cultivars, the cultivar Majid was superior in all vegetative growth characteristies, as compred with cv. Aulla, for both growing seasons. As for interactions among treatments, they were significant in thair effects on vegetative growth characteristies and for both seasons.